1980
DOI: 10.1007/bf00016762
|View full text |Cite
|
Sign up to set email alerts
|

Water chemistry changes during artificial aeration of spruce Knob Lake, West Virginia

Abstract: The water mass below 3 .5 m in Spruce Knob Lake was artificially aerated with a modified full lift aerator during two consecutive summers (1974 and 1975) of an investigation that began in July of 1973 and ended in September, 1975 . Artificial aeration increased water temperature below 3 .5 m without causing destratification . Several chemical parameters were significantly affected by artificial aeration, especially from July to autumnal overturn in 1974 and 1975 . Below 3.5 m, total inorganic carbon, total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…(1996), more than four aerators were required to allow sufficient circulation to prevent the formation of an anoxic water layer. An increase in water temperatures in the hypolimnetic layer and the earlier turnover in autumn under the condition of insufficient destratification by artificial aeration has been observed in other studies (Bernhardt 1967; Toetz 1977; Labaugh 1980). The maximum water temperature in the hypolimnetic layer had risen to ≈ 25°C from < 20°C before 1992 and the autumn turnover has occurred earlier by > 1 month (i.e.…”
Section: Resultssupporting
confidence: 80%
“…(1996), more than four aerators were required to allow sufficient circulation to prevent the formation of an anoxic water layer. An increase in water temperatures in the hypolimnetic layer and the earlier turnover in autumn under the condition of insufficient destratification by artificial aeration has been observed in other studies (Bernhardt 1967; Toetz 1977; Labaugh 1980). The maximum water temperature in the hypolimnetic layer had risen to ≈ 25°C from < 20°C before 1992 and the autumn turnover has occurred earlier by > 1 month (i.e.…”
Section: Resultssupporting
confidence: 80%
“…In contrast to the results of the Naukuchiytal lake regarding phosphorus, several workers have reported lower concentration of phosphate phosphorus during aeration in their respective studied water bodies (e.g. La Baugh, 1980;Burgi and Stadelman, 2002). Several other studies have found accumulation of phosphorus in the hypolimnion and reduction of it in the epilimnion and metalimnion due to aeration (Grochowska and Gawronska, 2004, Engstorm, 2005Liboriussen et al, 2009).…”
Section: Phosphate-phosphoruscontrasting
confidence: 56%
“…At Lake Waccabuc, New York, Fast (9) reported spring increases and summer decreases in secchi disk readings during the second year of aeration. At Spruce Knob Lake, West Virginia, La Baugh (12,13) reported lower chlorophyll a levels during the second year of aeration, but attributed this to destratification rather than to the effects of hypolimnetic aeration. Hickel (11) gives a detailed account of phytoplankton successional patterns at Grebner See, F.R.…”
Section: Introductionmentioning
confidence: 99%